2019
DOI: 10.1021/acsami.8b22262
|View full text |Cite
|
Sign up to set email alerts
|

Nanopillared Surfaces Disrupt Pseudomonas aeruginosa Mechanoresponsive Upstream Motility

Abstract: Pseudomonas aeruginosa is an opportunistic, multidrug-resistant, human pathogen that forms biofilms in environments with fluid flow, such as the lungs of cystic fibrosis patients, industrial pipelines, and medical devices. P. aeruginosa twitches upstream on surfaces by the cyclic extension and retraction of its mechanoresponsive type IV pili motility appendages. The prevention of upstream motility, host invasion, and infectious biofilm formation in fluid flow systems remains an unmet challenge. Here, we descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…Mitigating microbial infection and contamination remains a global challenge, spurring the continued development of a diverse range of antimicrobial technologies and biomaterials. There are two main approaches to producing antimicrobial surfaces: using either a material that incorporates microbiostatic antimicrobial agents such as cationic compounds, antibiotics, or silver or microbiocidal topographical nanopatterns to physically interact with microbes, thereby inhibiting the growth of these organisms. Although the first strategy is effective and can have simple preparation, antimicrobial agents may have limitations in terms of stability and longevity. Moreover, microbes can develop antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Mitigating microbial infection and contamination remains a global challenge, spurring the continued development of a diverse range of antimicrobial technologies and biomaterials. There are two main approaches to producing antimicrobial surfaces: using either a material that incorporates microbiostatic antimicrobial agents such as cationic compounds, antibiotics, or silver or microbiocidal topographical nanopatterns to physically interact with microbes, thereby inhibiting the growth of these organisms. Although the first strategy is effective and can have simple preparation, antimicrobial agents may have limitations in terms of stability and longevity. Moreover, microbes can develop antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, under flow conditions, bacteria uses their extracellular appendages to manure, 42 or swim upstream. 94 Further, it has been observed that bacterial growth increases with increasing fluid shear. 95 Bacterial phenotyping and biofilm density are also known to be influenced by the fluid shear rate.…”
Section: Measuring Bacterial Viability On Mnssmentioning
confidence: 99%
“…Induced by external factors, sometimes the bacteria also use passive motion. Interestingly, upstream swimming by E. coli, [122][123][124] and P. aeruginosa 94 under dynamic conditions is stimulated by various environmental factors such as changes in uid shear 124 or surface topography of substrates. 94 Bacteria are also known to be sensitive to external uid ow and shear rate.…”
Section: Bacterial Activities Under Dynamic Culture Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoimprint lithography (NIL) [17] is a suitable candidate to realize bioinspired patterns, as it is a high-resolution lithographic method with generally low cost, high throughput and the ability to use different substrates materials, allowing surface structuring of transparent and flexible materials [18] . Several examples of bio-inspired topographies fabricated by batch-to-batch NIL can be found in the literature based on one-level nanocones [19] , nanopillars [20] , [21] , [22] , [23] , [24] , micro lines [25] and micro mushrooms [26] . Using NIL is possible to fabricate multi-scale topographies combining micro- and nano-structures, denoted as hierarchical structures [27] , [28] , [29] , [30] , [31] , [32] , [33] .…”
Section: Introductionmentioning
confidence: 99%